Pengaturan Pola Makan Untuk Mengatasi Nyeri Pada Penderita Gastritis Di Klinik Spesialis Zam-Zam Jakarta Selatan - Hendrawati, Hendrawati; Septiana, Vinka; Ardilla, Nike (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to apply dietary arrangements to overcome acute pain in patients with gastritis at the Zamzam specialist clinic. The research method used is a type of descriptive qualitative research with a case study approach. The results of the study showed that after the intervention, heartburn pain was reduced and the pain scale became 1 and the client said that no nausea, vomiting, sour taste in the mouth and bloating decreased, for dietary arrangements after being educated, the respondents understood and abstained from eating spicy, sour, coconut milk, tea, coffee, milk. The conclusion obtained is that dietary adjustments can overcome pain in people with gastritis. Keywords: Gastirtis, Pain, Diet